Sensitisasi Alergen Makanan pada Pasien Kolitis Eosinofilik: Laporan Kasus - Zagoto, Agnes Dina Irene Dorithy; Mulya, Deshinta Putri; Ratnasari, Neneng (UI Scholars Hub, 2023)
Eosinophilic colitis is a very rare disease that can occur in the bimodal population (neonates and young adults) with a prevalence was 2.1/100,000 in overall population and 2.3/100,000 in adults. However, only about 0.1% of cases were diagnosed from biopsy results obtained during colonoscopy. The lack of precise histological criteria for the quantity of eosinophils in the colon mucosa creates a distinct challenge in diagnosing eosinophilic colitis. Eosinophilia in the gastrointestinal tract can be mediated by IgE and non-IgE, but non-IgE tends to be dominant in adults. This report discusses about a case of a 64-year-old male with bloody diarrhea that has been occur for two years. The anamnesis revealed symptoms suggestive of eosinophilic colitis, including complaints of diarrhea with abdominal pain and weight loss. Laboratory tests revealed an increase in peripheral eosinophil count and elevated levels of IgE. A positive skin prick test supported the presence of food allergen sensitization. The endoscopy revealed signs of ulcerative colitis, but the biopsy showed evidence of eosinophilic colitis. Initially, the patient was treated for ulcerative colitis but did not show improvement. Following treatment for eosinophilic colitis, the patient’s clinical status showed improvement. Since eosinophilic colitis can be chronic and recur, an accurate diagnosis and proper management are crucial for achieving complete remission. Keywords: chronic diarrhea, eosinophilic colitis, food allergen sensitization, IgE, peripheral eosinophilia